Investigating luxS gene expression in lactobacilli along lab-scale cocoa fermentations - Almeida, O.G.G.; Pereira, M.G.; Bighetti-Trevisan, R.L.; Santos, E.S.; De Campos, E.G.; Felis, G.E.; Guimarães, L.H.S.; Polizeli, M.L.T.M.; De Martinis, B.S.; De Martinis, E.C.P. (Food microbiology, 2024)
Previous metagenomic analyses have suggested that lactobacilli present potential for Quorum Sensing (QS) in cocoa fermentation, and in the present research, laboratory scale fermentations were carried out to monitor the expression of luxS, a universal marker of QS. For that, 96 h-fermentations were studied, as follows: F0 (non inoculated control), F1 (inoculated with yeasts, lactic acid bacteria, and acetic acid bacteria), F2 (inoculated with yeasts and acetic acid bacteria), F3 (inoculated with yeasts only). The parameters evaluated were: plate counting, quantification of key enzymes and analysis of volatile organic compounds associated with key sensory descriptors, using headspace gas chromatography-mass spectrometry (GC-MS). Furthermore, QS was estimated by the quantification of the expression of luxS genes by Reverse Transcriptase Real-Time PCR. The results demonstrated that microbial succession occurred in pilot scale fermentations, but no statistical differences for microbial enumeration and α-diversity index were observed among experiments and control. Moreover, it was not possible to make conclusive correlations of enzymatic profile and fermenting microbiota, likely due to the intrinsic activity of plant hydrolases. Regarding to the expression of luxS genes, in Lactiplantibacillus plantarum they were active along the fermentation, but for Limosilactobacillus fermentum, luxS was expressed only at early and middle phases. Correlation analysis of luxS expression and production of volatile metabolites evidenced a possible negative association of Lp. Plantarum with fermentation quality. In conclusion, these data corroborate former shotgun metagenomic analysis by demonstrating the expression of luxS by lactobacilli in pilot scale cocoa fermentation and evidence Lp. Plantarum is the main lactic acid bacteria related to its expression. •Pilot scale cocoa fermentations were carried out with selected microbial cocktails.•Both plant and microbial enzymes were likely active during fermentation.•The lux S gene was expressed in the fermentation, indicating quorum sensing activity.•Lactiplantibacillus plantarum was a key player for expression of luxS.•CG analysis of VOCs showed LAB could have negative impact on quality.